Mental health symptoms, spiritual well‐being and meaning in life among older adults living in nursing homes and community dwellings - Aydın, Adeviye; Işık, Abdullah; Kahraman, Nilgün (Wiley, 2020)
BackgroundAgeing is a process involving physical, social, psychological, spiritual and cultural changes. The elderly's personal characteristics may change, and the place where they live can lead to differences in their individual life expectations. Nursing home or community dwelling, where the elderly live can affect their psychological and spiritual well‐being and their search for meaning in life. This study aimed to determine mental health symptoms, spiritual well‐being and meaning in life among older adults living in nursing homes and community dwellings.MethodsThis cross‐sectional study was conducted in three provinces of Turkey with the highest population of elderly people aged 60 and above. A total of 144 elderly people (71 living in nursing homes and 73 in community dwellings) participated in the study. The Descriptive Information Form, Brief Symptom Inventory (BSI), Spiritual Well‐Being Scale and Meaning in Life Questionnaire were used for data collection. For the statistical analysis, the Kruskal–Wallis test, Mann–Whitney U‐test and Spearman correlation analysis were applied.ResultsAbout 42.3% of the elderly living in nursing homes were aged 80 and above, while 61.6% of those living in community dwellings were in the age range of 60–69 years. The hostility score in the community‐dwelling elders was statistically higher than that of elders living in nursing homes. However, the harmony with nature score was lower in the community‐dwelling elders. Negative relationships were found between total spiritual well‐being and depression, anxiety, negative self and somatisation. Meanwhile, existing meaning in life found positive relationships among transcendence and harmony with nature.ConclusionsThe awareness of healthcare workers is very important in helping the elderly make sense of the changes they experience. Moreover these healthcare workers should undergo systematic training to help the elderly prepare for old age by making sense of preserving mental integrity and seeking meaning in their lives.
Keywords: Aged, 80 and over; Male; mental health symptoms; Turkey; living in nursing home; community dwelling; Middle Aged; Nursing Homes; meaning in life; Cross-Sectional Studies; Mental Health; Quality of Life; Humans; Female; Spirituality; Independent Living; spiritual well-being; older adults; Aged; 3. Good health